Програмний комплекс моделювання складних систем на основі ітераційних алгоритмів МГУА з можливістю мережевого доступу - Bulgakova, О. S.; Zosimov, V. V.; Stepashko, V. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2014)
The structure of specialized modeling software based on iterative algorithms of the group method of data handling (GMDH) with the possibility of multiple access via the Internet or LAN is described. In the simulation software package implemented in three modes of dialogue — two automatic (standard and planning) and one interactive — where you can intervene in the process of self-organization models. The software works with different sets of data in Excel and Notepad text editor. The models construct of varying complexity and structure and with different sample decomposition. The best models are presented for the graphic system and semantic analysis and stored in the database along with the intermediate calculations and experimental results for later use. The system works with three databases: an initial database, database of intermediate calculations and results database.